Metabolic associated fatty liver disease increases the severity of COVID-19: A meta-analysis. Issue 2 (February 2021) - Pan, Lu; Huang, Pan; Xie, Xia; Xu, Jiachen; Guo, Dawei; Jiang, Yuan
Abstract: Background: The association between metabolic-associated fatty liver disease (MAFLD) and disease progression in patients with the coronavirus disease 2019 (COVID-19) are unclear. Aims: To explore the association between MAFLD and the severity of COVID-19 by meta-analysis. Methods: We conducted a literature search using PubMed, EMBASE, Medline (OVID), and MedRxiv from inception to July 6, 2020. Newcastle-Ottawa Scale (NOS) and Stata 14.0 were used for quality assessment of included studies as well as for performing a pooled analysis. Results: A total of 6 studies with 1, 293 participants were included after screening. Four studies reported the prevalence of MAFLD patients with COVID-19, with a pooled prevalence of 0.31 for MAFLD (95CI 0.28, 0.35, I 2 = 38.8%, P = 0.179). MAFLD increased the risk of COVID-19 disease severity, with a pooled OR of 2.93 (95CI 1.87, 4.60, I 2 = 34.3%, P = 0.166). Conclusion: In this meta-analysis, we found that a high percentage of patients with COVID-19 had MAFLD. Meanwhile, MAFLD increased the risk of disease progression among patients with COVID-19. Thus, better intensive care and monitoring are needed for MAFLD patients infected by SARS-COV-2.